Ocorrência e aspectos socioambientais de uma espécie de molusco exótica invasora no Baixo São Francisco e sua utilização como bioindicador de qualidade da água - Calazans, Denis Rocha (2014)
This work analyzes theoccurrenceof the mollusk Corbicula fluminea (Muller, 1774), in a 78 km stretch of the lower São Francisco river. C.fluminea is an exotic invading species that hás become dominant among benthic macroinvertebrates in the São Francisco river. The work aimed to assess its occurrence and the perceptions of local communities with the invasive species. A survey of the occurrence of C.fluminea was performed in two periods, winter and summer, at ten sampling points. A marginal village was chosen to make interviews about the relationship between the community and the bivalve. The study demonstrated that the occurrence of C.fluminea is not regular and presents density values above what is reported in the literature, which indicates that the bivalve reached or is close to reaching its occupational peak.The invasion caused an increase in the number of shells in riverbed, bad smell and attraction of birds when water level decreases, due to death and decomposition of mollusks, and may be related to the increase in the density of macrophytes in the studied river stretch. Local communities did not assimilate the presence of the shellfish, which does not yet have a local popular name nor was incorporated into their fishing or food habits.The study also evaluated the use of C.fluminea as a bioindicator of water quality, evaluatedthe quality of the water consumed by the population of a marginal village, and the perception of the residents of this village on the water they consume. The water distributed in the village showed to be inadequate for human consumption. The villagers do not have the habit to disinfect the water, which may be associated with diarrhea cases occurring in the community. It wasfoundthatinter-relationshipbetween the density occursof C.fluminea with the concentrations of total and fecal coliforms over eight months of monitoring, which involved both the rainy and dry seasons. Therefore, the use of C.fluminea as bioindicator of water quality in the lower São Francisco proved feasible,can reduce the costs of monitoring and provide more immediate answers to protect public health. This work analyzes theoccurrenceof the mollusk Corbicula fluminea (Muller, 1774), in a 78 km stretch of the lower São Francisco river. C.fluminea is an exotic invading species that hás become dominant among benthic macroinvertebrates in the São Francisco river. The work aimed to assess its occurrence and the perceptions of local communities with the invasive species. A survey of the occurrence of C.fluminea was performed in two periods, winter and summer, at ten sampling points. A marginal village was chosen to make interviews about the relationship between the community and the bivalve. The study demonstrated that the occurrence of C.fluminea is not regular and presents density values above what is reported in the literature, which indicates that the bivalve reached or is close to reaching its occupational peak.The invasion caused an increase in the number of shells in riverbed, bad smell and attraction of birds when water level decreases, due to death and decomposition of mollusks, and may be related to the increase in the density of macrophytes in the studied river stretch. Local communities did not assimilate the presence of the shellfish, which does not yet have a local popular name nor was incorporated into their fishing or food habits.The study also evaluated the use of C.fluminea as a bioindicator of water quality, evaluatedthe quality of the water consumed by the population of a marginal village, and the perception of the residents of this village on the water they consume. The water distributed in the village showed to be inadequate for human consumption. The villagers do not have the habit to disinfect the water, which may be associated with diarrhea cases occurring in the community. It wasfoundthatinter-relationshipbetween the density occursof C.fluminea with the concentrations of total and fecal coliforms over eight months of monitoring, which involved both the rainy and dry seasons. Therefore, the use of C.fluminea as bioindicator of water quality in the lower São Francisco proved feasible,can reduce the costs of monitoring and provide more immediate answers to protect public health.